Randai Arts Extracurricular Management (Case Study at Padang 6 State High School) - Evandi, Patricia; Ismaniar, Ismaniar (Universitas Negeri Padang, 2023)
This research is motivated by the uniqueness of the phenomena that exist in the randai arts extracurricular at N 6 Senior High School, namely this extracurricular has not too many devotees or the participants from this extracurricular are very few compared to the extracurricular active in the N 6 Padang High School, but the achievement What this extracurricular gets is a lot. The purpose of this study is to find out how the management of randai extracurriculars at the N 6 Padang High School. This research uses a qualitative approach, with a case study research method. The data sources in this study were the Randai extracurricular builder, the head of the extracurricular team and several members of this extracurricular. The data collection techniques used in this study were observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The data validity technique is by using method triangulation, source triangulation, and theoretical triangulation. The results showed that (1) in this extracurricular planning component, they conduct a briefing before starting the activity (2) the form of organization in this extracurricular is by grouping in each field, namely the music group, movement group, and dance group (3) on the components This extracurricular activity is predominantly carried out by the coach and team leader (4) the supervision carried out by the coach at this time is only via whatsapp because of the busyness that is being faced by the coach. Overall, the management of the randai extracurricular at SMA N 6 is very good, because it has followed the components of good management, which has made the randai extracurricular has many achievements.